Pregnancy with papillary serous cyst neoplasmseries of three cases - Bhutoria, BJ; Chattopadhyay, S; Banerjee, U; Jana, N (Journal of Pathology of Nepal, 2013)
Papillary serous neoplasm with pregnancy is a rare occurrence. Three such cases are presented here. In each case ovarian cyst was detected on ultrasonography when patients presented with non specific abdominal pain though there was no prior history or complaint on first antenatal visit. One is a papillary serous cystadenocarcinoma with capsular invasion in a twenty five year old woman and the other two are papillary serous tumour of borderline category in twenty and twenty three year old woman respectively. In the former pregnancy was terminated at 22 weeks followed by chemotherapy. In the other two cases pregnancy was continued and outcome was uneventful. DOI: http://dx.doi.org/10.3126/jpn.v3i6.9003 Journal of Pathology of Nepal (2013) Vol. 3, 505-508